Evaluación y caracterización de ácidos orgánicos presentes en cuatro bebidas ancestrales fermentadas tradicionalmente. - Chimba Amaya, Roberto Mauricio (2021)
Within the culture of the peoples and nationalities of eastern Ecuador, a millenary tradition is carried out, which consists of the production of fermented beverages, for which they use the yucca and chonta typical of the region, with the yucca three varieties of chicha that are white, black and wiwis, these drinks are consumed in rituals and festivities of ancestral peoples. We worked with the Kichwa Artisan Association of Pastaza "Agua Viva", who made these fermented drinks using traditional techniques, from which samples were collected to carry out the respective physical-chemical, microbiological analysis and characterization of organic acids. The analysis of organic acids was carried out in the Food Analysis and Research laboratory of the National Institute of Agricultural Research (INIAP) - Santa Catalina Experimental Station, by means of the high efficiency liquid chromatography (HPLC) method, this analysis consists of performing a conditioning, agitation, centrifugation, filtration, and the extraction of the mobile phase, to go on to the identification of organic acids, using lactic, tartaric, succinic and malic acid standards. According to the results obtained, the concentration of the organic acids present in the beverages was determined, in each of these there is a predominant acid, thus, in the three cassava beverages, lactic acid has a higher concentration, indicating that it is the predominant one. then we have that the concentration of lactic acid in the white chicha is 894.41 mg / 100ml, in the black chicha it is 802.38 mg / 100ml, and in the wiwis chicha it is 652.12 mg / 100ml. While in chicha de chonta the predominant acid according to its concentration was succinic acid with a value of 844.07 mg / 100ml and the absence of tartaric acid stands out. The concentration and presence of each acid within the beverages provides unique sensory characteristics, so the presence of lactic acid helps regulate the pH to ideal levels for fermentation, as well as providing a pleasant acid taste. Malic acid enhances flavors and aromas, attenuates sweetness and provides an acidic medium during fermentation. Tartaric acid acts as an acidifying agent and leaves a feeling of freshness. Succinic acid provides a bitterness to the drink.